Prevalence of Prehypertension in a Rural District of Southern India - Ravi, Marinayakanakoppalu R. (Int J Prev Med, 2015)
BACKGROUND: Estimating the prevalence of prehypertension and its risk factors in a population becomes important to design preventive measures and hence reduce the burden of hypertension.The aim of this study was to estimate the prevalence of prehypertension and determine the factors associated with hypertension. METHODS: This is a cross-sectional study and was carried out in a rural population. The study included 402 participants. Data regarding basic demographic characteristics were collected along with anthropometric measurements including height and weight. Information regarding smoking alcohol intake, dietary habits were collected. Prehypertension was defined as systolic blood pressure 120–139 mm Hg and/or diastolic blood pressure 80–89 mm Hg. Chi-square-test was used to find the association of various risk factors; t-test was used to compare the means. Multiple linear regression analysis was used to know the relationship of various risk factors. RESULTS: Prevalence of prehypertension was estimated to be 28.8%. Factors such as salt intake, tobacco consumption, alcohol consumption, stress, family history of hypertension, history of diabetes mellitus had a significant association with prehypertension (P < 0.05). CONCLUSIONS: The prevalence of prehypertension was found to be high among the rural population. Early intervention is needed to decrease the burden of hypertension and its complications in future.